A systematic review and meta-analysis of the association between unintended pregnancy and perinatal depression - Abajobir, A.; Maravilla, J.; Alati, Rosa; Najman, J. (Elsevier BV, 2016)
© 2015 Elsevier B.V. All rights reserved. Background There is a growing interest in exploring maternal mental health effects of unintended pregnancies carried to term. However, the evidence base from a small number of available studies is characterised by considerable variability, inconsistency and inconclusive findings. We present a systematic review and meta-analysis of all available studies on unintended pregnancy as these are related to maternal depression. Methods Using PRISMA guideline, we systematically reviewed and meta-analysed studies reporting an association between unintended pregnancy and maternal depression from PubMed, EMBASE, PsychINFO and Google Scholar. We used a priori set criteria and included details of quality and magnitude of effect sizes. Sample sizes, adjusted odds ratios and standard errors were extracted. Random effects were used to calculate pooled estimates in Stata 13. Cochran's Q, I2 and meta-bias statistics assessed heterogeneity and publication bias of included studies. Results Meta-bias and funnel plot of inverse variance detected no publication bias. Overall prevalence of maternal depression in unintended pregnancy was 21%. Unintended pregnancy was significantly associated with maternal depression. Despite statistically significant heterogeneities of included studies, sub-group analyses revealed positive and significant associations by types of unintended pregnancies, timing of measurements with respect to pregnancy and childbirth, study designs and settings. Conclusions The prevalence of perinatal depression is two-fold in women with unintended pregnancy. Perinatal care settings may screen pregnancy intention and depression of women backed by integrating family planning and mental health services.